Pengaruh Rekrutmen, Seleksi, Dan Penempatan Kerja Terhadap Kinerja Karyawan Pada PT. PLN (Persero) Unit Pelaksana Pembangkitan Teluk Sirih, Teluk Kabung Kecamatan Bungus Kota Padang - Caniago, Rita SrihasnitaRosali; Hirma, Dian; Aulia, Adilla (LPPM Universitas Dharma Andalas, 2023)
The purpose of this study was to determine how much influence recruitment, selection and job placement have on employee performance at PT PLN (Persero) Teluk Sirih Generation Implementation Unit, Teluk Kabung, Bungus District, Padang City. The research method used is quantitative with a sample of 123 respondents, data collection methods used are questionnaires and questionnaires. The results of the t-test in this study were partially recruited (X1), the value of tcount > ttable (4.149 > 1.657) with a significant value of 0.000 <0.05, meaning that the recruitment variable partially had a positive and significant effect on employee performance. The selection variable on employee performance has a value of tcount < ttable (1.131 < 1.657) with a significant value of 0.260 > 0.05, meaning that partially the selection variable has no positive and significant effect on employee performance. The variable of job placement on employee performance has a value of tcount > ttable (6.139 > 1.657) with a significant value of 0.000 <0.05, meaning that partially variable placement has a positive and significant effect on employee performance. The results of the F test found that recruitment, selection, and work placement together had a positive and significant effect on employee performance at PT PLN (Persero) Teluk Sirih Generation Implementation Unit, Teluk Kabung, Bungus District, Padang City, with a significant value < 0.05 The results of the coefficient of determination test are known to be the Adjusted R Square value with a value of 0.684 or 68.4%, meaning that the independent variable influence (Recruitment (X1), Selection (X2) and Work Placement (X3)) on the influence variable of Employee Performance (Y) is 68.4%, the remaining 31.6% is influenced by other variables not explained in this study